Perceptual-cognitive expertise and simulation-based training in sport - Williams, A. M. (Skill acquisition in sport: research, theory and practice, 2020)
In many sports, the ability to anticipate what will happen next is crucial to successful performance. The ability to anticipate is paramount because the speed of play dictates that athletes do not have time to react to an opponent`s actions due to the time needed to choose and initiate the appropriate response. In fast ball sports such as tennis, baseball, and cricket, athletes often have to strike a ball travelling in excess of 160 kilometers per hour, whereas in soccer and the various codes of hockey the ball or puck can travel from the penalty line/spot to the goal in less than 500 msec. The need to anticipate is not only paramount in ball sports; it is critical to performance in many other sports that do not involve a ball or projectile such as sailing, the combat sports (e.g., boxing, karate), speed skating, and skiing. In light of the importance of anticipation in high-performance (and recreational) sport, scientists have focused on trying to answer two key questions. First, how are athletes able to anticipate and what are the key skills underpinning superior performance? Second, how are these underlying skills developed and can we promote more rapid acquisition of these skills using various training interventions? In this chapter, it is not the intention to provide an all encompassing review of literature on simulation-based training, or more broadly to review research that has used other methods to develop perceptual-cognitive expertise. The scope is delimited to focus primarily on two key questions that have yet to be adequately addressed through relevant empirical work. The first question concerns how training programs that recreate the demands placed on athletes during actual competition might be developed. In reality, perceptual training programs are focused on enh ancing a single perceptual-cognitive skill, under controlled conditions, in the laboratory. The second question is closely related to the first, that is, how do we effectively measure whether any improvements observed in training actually transfer to performance in competition? An overview of the key skills underpinning perceptual-cognitive expertise in sport is necessary before addressing these two questions.